Sensors for Next-Generation Robotics III 2016
DOI: 10.1117/12.2225411
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive pressure sensor array for robotic skin

Abstract: Robots are starting to transition from the confines of the manufacturing floor to homes, schools, hospitals, and highly dynamic environments. As, a result, it is impossible to foresee all the probable operational situations of robots, and preprogram the robot behavior in those situations. Among human-robot interaction technologies, tactile sensing is an intuitive physical interaction method that can help define operational behaviors for robots cooperating with humans. Multimodal robotic skin with distributed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Among them, PDMS are suitable for EHD printed electronics. Recent studies focus on fabricating flexible pressure and strain sensor array [143,144], ion-gel-based transistor [145], flexible electrodes [146][147][148], organic thin-film transistor (OTFT) [149,150] etc. Although PEDOT: PSS is commonly used in printed electronics, the ink properties, geometrical pattern and array can be further optimized for targeted applications and multi-modal sensor integration.…”
Section: Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, PDMS are suitable for EHD printed electronics. Recent studies focus on fabricating flexible pressure and strain sensor array [143,144], ion-gel-based transistor [145], flexible electrodes [146][147][148], organic thin-film transistor (OTFT) [149,150] etc. Although PEDOT: PSS is commonly used in printed electronics, the ink properties, geometrical pattern and array can be further optimized for targeted applications and multi-modal sensor integration.…”
Section: Polymersmentioning
confidence: 99%
“…These 3DP techniques have already been demonstrated as effective methods in physical sensors fabrication, with many sensor devices successfully fabricated. The 3DP physical sensors include tactile (touch sensors) [173,204], acoustic sensors [205,206], microcantilever sensors [207], transistors [145,[148][149][150]208,209], strain sensors [143,171,172,210], pressure sensors [66,135,144,151,154,170,211,212] and (piezo resistance, piezoelectricity, capacitance, triboelectricity), photosensors [213][214][215][216]. etc.…”
Section: Electronic 421 Physical Sensormentioning
confidence: 99%
“…On the other hand, organic semiconductors can be PEDOT: PSS, rubrene, pentacene, poly(diketopyrrolopyrrole-terthiophene) (PDPP3T), diphenylanthracene (DPA) [43]. PEDOT: PSS and CNT-based composites are vastly used as pressure sensors (piezorresistive materials) [81,82], and temperature sensors (thermoresistive materials) [83,84].…”
Section: Functional Inks For Ijpmentioning
confidence: 99%
“…To enhance the capabilities of artificial skins various sensors embedded within these soft skins have been a part of literature. Mirza et al 32 demonstrated the fabrication and experimental characterization of piezoresistive pressure sensor array for robotic skin. Ha et al 33 reviewed the trends, challenges and perspectives of the importance of soft capacitive pressure sensors and their role in e‐skins.…”
Section: Introductionmentioning
confidence: 99%